Information technologies in the biology teaching system. - Toshpulatova D.S., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The process of expanding the use of new information technologies in various educational areas, including school biology, requires a serious analysis from the standpoint of the didactic and methodological validity of the use of certain tools in the specific conditions of the educational process.